Application of electric fields to mitigate inhibition on anammox consortia under long-term tetracycline stress. (December 2021) - Cheng, Benai; Bao, JianGuo; Du, Jiangkun; Tufail, Haseeb; Xu, Tiantian; Zhang, Yi; Mao, Qidi
Graphical abstract: Highlights: Electric field application mitigated inhibition of TC on anammox consortia. VEF was more suitable for 10 mg L −1 TC and 3 V was better for 2 mg L −1 TC. TB-EPS become a potential biomarker of nitrogen removal performance. The main mechanism of electric field was sludge structure strengthening. Abstract: The feasibility of applying electric fields to mitigate inhibition of tetracycline (TC) on anammox process and improve system stability was evaluated in this study. Three electric field intensities of 1, 3 and a variable intensity of 1–6 V (VEF) were used to optimize electric field intensity under gradually increasing addition of TC (0.5, 2 and 10 mg L −1 ). Results showed that the application of electric fields (3 V and VEF) could improve TC tolerance and keep relatively high-efficiency nitrogen removal performance, especially at TC ≥ 2 mg L −1 . Furthermore, applying electric fields contributed to mitigate irreversible inhibition and improve the stability of community structure. Underlying mechanism analysis indicated that the main mechanism of applying electric fields to mitigate inhibition relies on sludge structure strengthening. This study explored a novel strategy to reduce the inhibition of antibiotics on microbial denitrification and broaden the application of anammox in industrial water treatment.